2009
DOI: 10.1614/wt-08-097.1
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Curves of KIH-485 for Preemergence Weed Control in Corn

Abstract: Field experiments were conducted in Nebraska with the experimental herbicide KIH-485 on soils with three different levels of organic matter (OM) to ascertain a dose response for weed control and corn tolerance. Dose–response curves based on the log-logistic model were used to determine the effective dose that provides 90% weed control (ED90 values) for three grasses (green foxtail, field sandbur, large crabgrass) and two broadleaf weeds (velvetleaf, tall waterhemp). The ED90 values for green foxtail control we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 18 publications
7
60
1
1
Order By: Relevance
“…Studies have been reported using hyperbolic regressions for building doseresponse curves to other weed species (Bósnic & Swanton, 1997;Monquero, 1999;Knezevic et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Studies have been reported using hyperbolic regressions for building doseresponse curves to other weed species (Bósnic & Swanton, 1997;Monquero, 1999;Knezevic et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The curve was used to determine the dose of sulfentrazone required to obtain at least 95% of the soybean yield compared with the weed-free control. This percentage was based on the optimal yields reported in previous research (Knezevic et al 2009;Nurse et al 2010), and was deemed commercially acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…P y roxasu lfone(3-[5-(dif luoromet hoxy)-1-met hy l-3-(trifluoromethyl) pyrazol-4-ylmethylsulfonyl]-4,5-dihydro-5,5-dimethyl-1,2-oxazole; code name KIH-485) is a novel preemergence herbicide for use in wheat, 1) corn, [2][3][4][5][6] soybean 7) and other crops. 1,[8][9][10][11] This herbicide is effective on both grass and broadleaf weeds.…”
Section: Introductionmentioning
confidence: 99%